Reflection seismic imaging of the deeper structures at the Forsmark spent nuclear fuel repository site, central Sweden - Sharifi Brojerdi, F.; Juhlin, Christopher; Malehmir, A.; Stephens, M. (2013)
The Forsmark area belongs to the Paleoproterozoic Svecokarelian orogen (c. 1.9-1.8. Ga), the principal geological entity inside the Fennoscandian Shield, and is the site where Sweden has proposed to store its spent nuclear fuel. Three major sub-vertical (at the surface), composite ductile and brittle deformation zones that strike in a WNW or NW direction are present in the area. In between these zones the bedrock is less deformed and considered suitable for a repository. We present reprocessed reflection seismic data from seven profiles in which we have focused on improving the images in the depth range 1-5. km by passing lower frequencies through the processing flow at the cost of poorer resolution in the near-surface realm. The new images indicate that sub-horizontal to moderately dipping structures are possibly more extensive at depth than previously thought. Three main deeper reflective zones have been identified, one that is sub-horizontal and two that dip moderately to the southwest. The sub-horizontal reflective zone may represent a 1.27-1.26. Ga dolerite sill at about 3. km depth. One of the moderately dipping reflective zones may originate either from another dolerite sill or from a brittle fault system. The other moderately dipping structure may be present throughout most of the area and could cut all three sub-vertical deformation zones at depth. The new images and corresponding interpretation do not require a re-evaluation of the Forsmark site for storage of spent fuel, but they do influence how to interpret the deeper structures and, as a consequence, the tectonic evolution of the area. © 2012 Elsevier B.V.